Basic Principles of Interface Science and Colloid Stability : Basic Principles of Interface Science and Colloid Stability. - Tadros, Tharwat F. (De Gruyter reference., 2017)
Volume 1 of the Handbook of Colloid and Interface Science is a survey of the theory of colloids in a variety of fields, as well as theircharacterization by rheology. It is an ideal reference work for research scientists, universities, and industry practitioners looking for a complete understanding of how colloids and interfaces behave.